Why is inflation skewed? a debt and volatility story - Aizenman, Joshua 1949-; Hausmann, Ricardo (1994)
This paper studies the patterns of inflation skewness in 56 countries. Monthly data suggests that inflation is positively skewed. We investigate linkages between skewness and non-linearity, showing that concavity (convexity) will lead to negative (positive) skewness if the independent variable is symmetrically distributed. We construct a public finance model for a developing country that uses inflation tax and external borrowing as the residual means for fiscal financing. The model predicts a convex dependency of inflation on output, where inflation skewness depends positively on inflation volatility, and external debt difficulties magnify the skewness. We conclude the paper with an assessment of the patterns of inflation between 1979-1993 for the 56 countries. Overall, the patterns are consistent with the predictions of the model.
Keywords: Geschichte 1900-2000; Geschichte; Mathematisches Modell; Debts, External -- Mathematical models; Inflation (Finance) -- Mathematical models; Macroeconomics -- History -- 20th century